The training of teachers to work in rural schools in Siberia in late XIX–early XX centuries - O. V. Ishchenko (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the characteristics of the main directions of training of future national teachers in teachers’ seminaries of Siberia in the late XIX–early XX centuries in accordance with the state policy of primary education development. The objectives of the study were to analyze the government policy in the field of primary education development in rural areas, to characterize its implementation in the activities of teachers’ seminaries in Siberia, to assess the compliance of the result of teacher training with the stated state goals. The author has analyzed government documents, materials of educational institutions, historical and pedagogical scientific works. This made it possible to identify the content and goals of training seminarians for educational and cultural activities in rural areas. During the years of his stay at the seminary, the future teacher had to learn how to conduct lessons and educate children, develop them aesthetically, instill hygiene skills in them, organize leisure time, help peasant society in mastering of agricultural knowledge, etc. Finally, it is concluded that in the conditions of Siberia, there was the people’s teacher who became the main source of educational and cultural impact on the peasant environment, which corresponded to the tasks set for him by the state, but was not accompanied by the necessary financial support on his part.